Analisis Ketahanan Pangan Pasca Pandemi Kota dan Kabupaten di Provinsi Termiskin Kedua Pulau Sumatera - Wibowo, Hariz Eko; Novanda, Ridha Rizki; Ifebri, Rihan; Fauzi, Ariffatchur (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2024)
Food security is one of the maqashid of sharia (sharia goals), namely protecting the soul (hifz al-nafs). Food security is important in maintaining the life and sustainability of humanity. Because affordability is a component of food security, there is a close relationship between food security and poverty. Bengkulu Province is the second largest province with a percentage of people living in poverty on the island of Sumatra. However, the percentage of people in Bengkulu Province who live in poverty tends to be unaffected by the pandemic and is even showing signs of decreasing. The results of other studies on the impact of the pandemic on poverty, income and food security contradict this. Therefore, it is necessary to conduct research regarding changes in food security after the pandemic in cities and districts in Bengkulu Province. The results of this descriptive analysis show that almost all city and district food security indices have not experienced significant changes after the Covid-19 pandemic in Bengkulu Province. Only Mukomuko Regency and Bengkulu City experienced significant changes, namely changing from the "Resistant" category to "Very Resistant". The results of a deeper analysis based on the three aspects show that there are no significant changes in the three aspects from 2020-2023. Only Mukomuko Regency and Bengkulu City experienced a significant increase in the food utilization index from 2020-2023. This is in line with the descriptive analysis of the food security index where the increase in the food security index for Mukomuko Regency and Bengkulu City was caused by an increase in the food utilization index.